INFLUENCE OF ELECTRONIC WORD OF MOUTH ON E-COMMERCE CUSTOMER DECISION PROCESS IN INDONESIA - Anisa Nurul Rahma (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
E-commerce is a new concept that can be used as a process of buying and selling goods or services on the Word Wide Web Internet. This research aims to identify and analyse how much the influence of electronic word of mouth on purchasing decision process on e-commerce customers in Indonesia. This research uses one free variable independent electronic word of mouth and one bound variable dependent purchasing decision process. This research uses quantitative research methods using purposive sampling techniques. Samples taken as much as 100 respondents. Data collection techniques using questionnaires. The population in this research is the people of Jakarta who have used five top e-commerce in Indonesia (Tokopedia, Shopee, Bukalapak, Lazada, Blibli). Data analysis techniques use descriptive statistical analysis techniques and non-parametic analysis of simple linear regression analyses. The results showed that there was a significant influence between electronic word of mouth on purchasing decision process for e-commerce customers in Indonesia of 56 percent, while the remaining 44 percent were influenced by factors Other.